Optimizing the Role of Special Guidance Teachers (GPK) in Serving Children with Special Needs (ABK) at SMP Muhammadiyah 1 Kartasura - Rahmawati, Widia Wahyu; Ruhaena, Lisnawati; Ansori, Acep Azis; Hamtina, Metanisa Rofi (Universitas Muhammadiyah Surakarta, 2025)
This training aims to enhance the competencies of Special Education Teachers in assisting students with special needs at SMP Muhammadiyah 1 Kartasura. The program was conducted over two days and included material delivery, practical exercises in identifying special needs, and communication simulations in the classroom. The training participants, consisting of five special education teachers, were given pre-tests and post-tests to measure their improvement in understanding and skills. The results showed significant progress in observation, communication, and identifying special needs. Furthermore, interactive discussions during the training provided a platform for participants to share experiences and solutions to challenges in assisting Special Needs. This training serves as a strategic step in supporting the implementation of inclusive education, with the expectation that special education teachers can apply the skills learned to create a supportive and inclusive learning environment for special needs development.